Origin of teachers’ Colleges in Caldas Department, Colombia - Loaiza Zuluga, Yasaldez Eder (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper is the result of the research work “Origin of Teachers´ Colleges in Caldas Department”. The research followed chronologically the historical phases of the methodology: heuristics, doxography, etiology and historical synthesis, in order to understand the development of these institutions, from their beginnings to their current status as the recognized institutions for initial teacher training. Because of their role as the institutions charged with training the first levels of the Colombian educational cadres, it is possible through a study of their development to understand, interpret, characterize, describe the processes of scientific research of historical design; given that these institutions have been the field of action for the study of educational problems, rooted in historical, theoretical, practical, and experiential considerations. This historical-educational study covers the period between 1909,when the first Teachers College in Caldas was created, and 1978, when the approval of Decree 1419 changed the qualifications of teachers from being graduates of Teachers Colleges to holders of a degree of Bachelor of Pedagogy. This study documents the centralized and rigid way in which these teacher training institutions have been established and developed. Consequently, they can be characterized as institutions regulated by a narrow vision, in which the State exercises control over the discussions and pedagogical practices that build the school culture.